Reflective conversations as a basis for sport coaches' learning: a theory-informed pedagogic design for educating reflective practitioners - Stodter, Anna; Cope, Ed; Townsend, Robert C. (Professional development in education, 2024)
There is a clear need to design more effective professional learning environments, particularly in sport coaching as a developing educational profession. The purpose of this study was to investigate the interplay between theory-informed pedagogic design, the role of the coach developer, and sport coaches' perceived learning in a Higher Education online undergraduate module on reflective practice. The project involved designing a module based on domain-specific theories of coaches' learning and implementing multiple 'reflective conversations' with 21 professional association football coaches to structure their learning. Thematic analysis of data from 24 reflective conversations, five follow up semi-structured interviews and four focus group interviews, as well as a coach developer interview, determined perceptions of design, delivery and development. Findings demonstrated that theory-informed design and the aligned skill-set of the coach developer was significant in developing depth of participant coaches' understanding, and connecting theory to authentic reflective practice. The findings provide evidence to support the need for developing underpinning pedagogic design in the effectiveness of professional learning environments for developing reflective practitioners in educative professions such as sport coaching.